2022
DOI: 10.1038/s41467-022-27987-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping molecular subtype specific alterations in breast cancer brain metastases identifies clinically relevant vulnerabilities

Abstract: The molecular events and transcriptional plasticity driving brain metastasis in clinically relevant breast tumor subtypes has not been determined. Here we comprehensively dissect genomic, transcriptomic and clinical data in patient-matched longitudinal tumor samples, and unravel distinct transcriptional programs enriched in brain metastasis. We report on subtype specific hub genes and functional processes, central to disease-affected networks in brain metastasis. Importantly, in luminal brain metastases we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 70 publications
3
44
0
Order By: Relevance
“…5b and Supplementary Table 18 ). Analysis of the cohort of patients with breast cancer brain metastases 59 , 60 who were treated with radiotherapy confirmed the correlation between S100A9 expression levels and survival from brain metastasis diagnosis (Fig. 5e and Supplementary Table 16 ), which was reproduced by S100A8 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…5b and Supplementary Table 18 ). Analysis of the cohort of patients with breast cancer brain metastases 59 , 60 who were treated with radiotherapy confirmed the correlation between S100A9 expression levels and survival from brain metastasis diagnosis (Fig. 5e and Supplementary Table 16 ), which was reproduced by S100A8 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 56%
“…5a ), potentially suggesting that a specific subtype of melanoma brain metastases, not represented by available mouse models, could be the main contributor to S100A9 positivity. To score the clinical correlation with S100A9, several cohorts of patients with brain metastasis and lung cancer ( n = 22), breast cancer 59 , 60 ( n = 42) or melanoma ( n = 34) were selected based on the presence of patients who received neurosurgery followed by radiotherapy (Fig. 5a and Supplementary Tables 15 – 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PDO-PDOX approach to study BCBM metastases is an alternative promising approach for generating efficient BCBM preclinical models that have not yet been exploited. Recently, Cosgrove et al demonstrated that freshly resected BCBM tumours could be used to generate PDO and perform genomic and transcriptomic analysis to identify therapeutic vulnerabilities [123].…”
Section: Discussionmentioning
confidence: 99%
“…MMR testing could be used in clinical practice to help guide treatment based on immunotherapy, particularly in HER2 enriched and TN tumors as we found these to be more proportionally involved by MMR. Also, mutational signatures associated with MMR have been found to be enriched in breast cancer brain metastases compared to primary breast tumors 45 . Suggesting there may be a role of MMR and PD-L1 testing in metastatic breast cancer specimens.…”
Section: Discussionmentioning
confidence: 99%